Protection of hirer's interest under hire purchase transaction in Malaysia: the roles of ministry of domestic trade, co-operatives and consumerism - Ilias, Ibtisam@Ilyana; Hassan, Rusni; Kassim, Salina; Abu Bakar, Elistina (2017)
This paper examines the roles of Ministry of Domestic Trade, Co-operatives and Consumerism in protecting the hirer’s interest under the hire purchase transaction. In addition to a rigorous scrutiny on its regulatory powers and functions conferred by the Hire Purchase Act 1967, the ministry’s institutional and organisational set-up are also discussed in detail with a view of understanding the internal capacity in performing the functions and exercising the power. In implementing its regulatory role, the powers to issue regulation and to enforce the law via criminal action are adequately dealt with. This study discloses that the present institutional framework lacks one fundamental aspect of protection namely absence of licensing regime. Enforcement aspect is also tainted with some weaknesses in terms of nature of enforcement action to be pursued which merely relies on criminal action and the issue of human resources. The study therefore recommends firstly the establishment of licensing regime; secondly the incorporation of administrative and civil action as an addition to the existing enforcement power and thirdly the strengthening of current enforcement machineries.